Human resource management and project based organizing: Fertile ground, missed opportunities and prospects for closer connections. Issue 1 (January 2018) - Keegan, Anne; Ringhofer, Claudia; Huemann, Martina
Abstract: We explore publishing trends regarding HRM and PBO in the main journals in the field of project management to highlight key empirical and theoretical contributions during the period 1996–2016. We offer three contributions to the field of project management. The first is theoretical where we analyze twenty years of research in key project management journals by adapting and extending the framework of Wright and Boswell (2002), and identifying categories of HRM research at three levels of analysis. This analysis provides an overview integrating exemplary research to date on the HRM-PBO link at different levels, showing areas where research is well-developed and also areas that, while promising, have not been examined in a systematic manner to date. Our second contribution is that we highlight a variety of theoretical as well as methodological resources from the HRM field that can be applied in project studies and in so doing promote cross-fertilization of ideas and approaches between these two fields. Finally, a key managerial contribution is that we introduce the project as a temporary organization level of analysis, explicitly making visible HRM practices on the project. This can guide both HRM practitioners, and project managers, in terms of the importance of projects as sites for human resource management and employment activities including careers, employee participation and employment relations all of which are critical issues and deserve more attention. Highlights: We analyze publishing trends regarding HRM and PBO in the IJPM, PMJ and IJMPB during the period 1996 and 2016. We extend Wright & Boswell's (2002) schema and focus on exemplars of work on the HRM-PBO link. We discuss missed opportunities and prospects for closer connections regarding HRM-PBO based on a review of published work.